Cocaine-Associated Myocardial Infarction: Should They All Be Stented? - Sazzli Kasim; Ronan O'Donabhain; Eugene Mcfadden (Case Reports in Cardiology)
Cocaine use is a known cause of chest pain and acute myocardial infarction and frequently leads to cardiac catheterization procedure. The treatment of cocaine-related acute coronary syndromes presents unique challenges because a variety of mechanisms including atherosclerotic plaque rupture, platelet activation, and coronary vasospasm may contribute to the pathogenesis. Our case highlights important considerations taken in dealing with this acute scenario